Effects of Health Shocks on Adult Children's Labor Market Outcomes and Well-Being - Eduardo Ramirez Lizardi; Elisabeth Fevang; Knut Røed; Henning Øien (Institute of Labor Economics (IZA), 2024)
Using Norwegian administrative register data, we assess the impact of health shocks hitting lone parents, specifically stroke and hip fractures, on labor market outcomes and the well-being of adult offspring. We identify small, but statistically significant immediate responses in terms of an increase in physician-certified sickness absences and a higher risk of diagnosed mental disorders. However, these effects tend to fade out quickly, and the negative impacts on subsequent employment and earnings are small and only borderline statistically significant. In general, our results suggest that the responses to the deteriorating health of a parent tend to be short-lived and mostly manifest as temporary absences from work rather than complete detachment from the labor market.
Keywords: I12; I31; J14; J22; 330; health shocks; labor supply; mental health; informal care; parental health; event-studies